Konsep Musyarakah menurut Syeikh Daud Al-Fatani dalam Furuâ€˜ Al-MasÃ¢â€™il - Hadenan bin Towpek (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2010)
This paper presents Sheikh Daud al- Fataniâ€™s thought on the concept of Musharakah in his book Furu 'al-Masa'il and referred specifically to the Kitabal-Shirkah. How musyarakah generally applied in Malaysia's Islamic banking system is the focus of this paper. In the same period, cross-references with the valid views of jurists of al- Shafi'i school of thought are also applied. Moreover, the concept of Musharakah is presented in his book â€œFuru 'al-Masa'ilâ€ is still considered relevant and applicable, including in the field of Islamic banking and finance from the past, present and future.